2016
DOI: 10.1159/000444900
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine in Renal Injury

Abstract: Background: Homocysteine (Hcy) is an intermediate of methionine metabolism. Hyperhomocysteinemia (HHcy) can result from a deficiency in the enzymes or vitamin cofactors required for Hcy metabolism. Patients with renal disease tend to be hyperhomocysteinemic, particularly as renal function declines, although the underlying cause of HHcy in renal disease is not entirely understood. Summary: HHcy is considered a risk or pathogenic factor in the progression of chronic kidney disease (CKD) as well as the cardiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 66 publications
4
67
1
Order By: Relevance
“…In the general population, serum homocysteine level is associated with age and renal function [30]. However, in this study, premature CAD patients with better renal function and younger age showed a higher level of homocysteine.…”
Section: Discussioncontrasting
confidence: 67%
“…In the general population, serum homocysteine level is associated with age and renal function [30]. However, in this study, premature CAD patients with better renal function and younger age showed a higher level of homocysteine.…”
Section: Discussioncontrasting
confidence: 67%
“…This is in agreement with a recent work which reported that renoprotection was offered via post‐RIC through an adenosine‐independent mechanism . There are multiple studies which found that HHcy induces renal dysfunction . It is highly likely that RIC uses similar signaling pathways in improving the renal functions; however, there is no research that has been undertaken in the past to uncover whether RIC can afford protection in renal injuries caused by HHcy.…”
Section: Protection Of the Target Organs Via Ricsupporting
confidence: 90%
“…Oxidative stress is viewed as a critical pathogenic factor in the initiation, development, and progression of most renal diseases [14][15][16].…”
Section: Discussionmentioning
confidence: 99%